If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(14)(2)+2x+32=70
We simplify the equation to the form, which is simple to understand
(14)*(2)+2x+32=70
Reorder the terms in parentheses
multiplication of parentheses
(+28)+2x+32=70
Remove unnecessary parentheses
+28+2x+32=70
We move all terms containing x to the left and all other terms to the right.
+2x=+70-28-32
We simplify left and right side of the equation.
+2x=+10
We divide both sides of the equation by 2 to get x.
x=5
| 4lnx-7=1 | | -4(x+4)-2=-18 | | -0.5*32x^2+24x+50=0 | | x^3+6x^2+9x=5 | | 10x+1=2x+73 | | (-1+i)-(-2-i)=0 | | -50+8x=5x+52 | | x^3+3x^2-3x=0 | | (5x+10)+7x= | | -3(x-4)+4=-4(3x-3)+6+13x | | 16m=76 | | 2x-5y=-25 | | 4(3x+8)=80 | | 6(5x+11)-9x= | | 35=-7+3n | | 23n-24n= | | 2=15x^2+x | | y=0.13x+585 | | 4(3n+3)=9(9n+1)+5 | | (x-(8/x))^2-5(x-(8/x))-14=0 | | 12x-127=4x+169 | | (8x^4-2x^2+3x-5)-(2x^4+x^3+3x+5)= | | (3x+3)+(15-3x)= | | 7(2n+2)=7(7n+7)+9 | | 4(q)+(-1)(1-q)=1(q)+2(1-q) | | -4n(6n-5)+3n= | | 5(x+3)=4x+14 | | 0.9x-5.3=0.1 | | (9x-6)+6= | | 2+-6m=-4m+10 | | -9(y-1)=2-8y | | -3x(x+5)-7=-8+10 |